Barbell Technique Associated With Sinus Lift for Horizontal and Vertical Guided Bone Regeneration—Case Report - Fernanda Calvo Costa; Thaís Cachuté Paradella; Fernando Vagner Raldi; Michelle Bianchi-de Moraes; Rodrigo Dias Nascimento (Case Reports in Dentistry)
Conclusion: In this clinical case, for the first time in the literature, the association of the techniques allowed the regeneration of the defect, with the subsequent placement of implants in the ideal position and prosthetic rehabilitation.